Kwashiorkor on the south shore - Arcieri, Samuel T. (J Community Hosp Intern Med Perspect, 2021)
Kwashiorkor syndrome is a form of severe protein-energy malnutrition characterized by protein deficiency and bilateral extremity swelling. Worldwide, most affected regions include Southeast Asia, South Africa and Central America; it is rare in developed countries such as the USA. We report a case of profound kwashiorkor in a 38-year-old male with an underlying psychiatric disorder and restricted diet who presented with extensive abdominal distention and systemic findings indicative of protein malnutrition.